Evgeny Preobrazhensky and His Attempt to Renewal the Social-Economic Thought - Alexandru TRIFU (International Journal of Social and Educational Innovation, 2017)
In presenting the unfolding of the Economic Thought during decades and centuries, in order to fill the gaps in this holistic vision, or to highlight some aspects in time and space, we found it necessary to evidence one of these moments. It is about the third decade of the 20th century, in USSR, starring in the spotlight the thinker and politician Evgeni Alekseyevich Preobrazhensky (1886- 1937). He was the thinker, in the troubled period after Lenin‟s death and Stalin‟s rising, by trying background and imposing of so-called New Economic Policy (NEP), but very well to be understood as The New Economics. Better said, he tried to find theoretical features to support this policy, which emerged and was implemented in the early Bolshevik years after WWI in Russia/USSR. The important ideas and measures stipulated by Preobrazhensky resist decades and are still valuable in our days.The study of Preobrazhensky‟s writings must be done, either in the context of his doctrinal era, including famous thinkers as Alfred Marshall or John Maynard Keynes and in the context of today‟s approach on Political Economy.